There Is More to Mindfulness Than Emotion Regulation: A Study on Brain Structural Networks - Baltruschat, Sabina; Cándido, Antonio; Maldonado, Antonio; Verdejo-Lucas, Carmen; Catena-Verdejo, Elvira; Catena, Andrés (Frontiers in Psychology, 2021)
Dispositional mindfulness and emotion regulation are two psychological constructs closely interrelated, and both appear to improve with the long-term practice of mindfulness meditation. These constructs appear to be related to subcortical, prefrontal, and posterior brain areas involved in emotional processing, cognitive control, self-awareness, and mind wandering. However, no studies have yet discerned the neural basis of dispositional mindfulness that are minimally associated with emotion regulation. In the present study, we use a novel brain structural network analysis approach to study the relationship between structural networks and dispositional mindfulness, measured with two different and widely used instruments (MAAS and FFMQ), taking into account the effect of emotion regulation difficulties. We observed a number of different brain regions associated with the different scales and dimensions. The total score of FFMQ and MAAS overlap with the bilateral parahippocampal and fusiform gyri. Additionally, MAAS scores were related to the bilateral hippocampus and the FFMQ total score to the right insula and bilateral amygdala. These results indicate that, depending on the instrument used, the characteristics measured could differ and could also involve different brain systems. However, it seems that brain areas related to emotional reactivity and semantic processing are generally related to DM, regardless of the instrument used.